2015
DOI: 10.1111/iep.12124
|View full text |Cite
|
Sign up to set email alerts
|

A novel technique for simultaneous whole‐body and multi‐organ decellularization: umbilical artery catheterization as a perfusion‐based method in a sheep foetus model

Abstract: The aim of this study was to develop a method to generate multi-organ acellular matrices. Using a foetal sheep model have developed a method of systemic pulsatile perfusion via the umbilical artery which allows for simultaneous multi-organ decellularization. Twenty sheep foetuses were systemically perfused with Triton X-100 and sodium dodecyl sulphate. Following completion of the whole-body decellularization, multiple biopsy samples were taken from different parts of 21 organs to ascertain complete cell compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 111 publications
1
11
0
Order By: Relevance
“…The work of Franklin Mall over a century ago 1 , 2 , as well as modern-day decellularization techniques 3 , demonstrate that there are “reticular networks” made up of collagens, elastin, glycosaminoglycans, and other extracellular matrices (ECM) components surrounding, within, and between organs. These networks have biological and mechanical roles in defining the architecture and physiology of organs and, as a result, are now used as scaffolding for the creation of customized organ grafts for regenerative medicine 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The work of Franklin Mall over a century ago 1 , 2 , as well as modern-day decellularization techniques 3 , demonstrate that there are “reticular networks” made up of collagens, elastin, glycosaminoglycans, and other extracellular matrices (ECM) components surrounding, within, and between organs. These networks have biological and mechanical roles in defining the architecture and physiology of organs and, as a result, are now used as scaffolding for the creation of customized organ grafts for regenerative medicine 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Continuity between mesenteric fascia and the connective tissues of the small intestinal and colonic walls has also been previously recognized 6 – 9 . More recently, the decellularization of entire fetal sheep shows that the connective tissue network is continuous throughout the body and that the connective tissue of nerves creates structural continuity between the nervous system and other tissues 3 . Dissection of human bodies likewise demonstrates continuity across large, multiorgan regions of the body, including the entirety of the dermis and the fascia of diverse organs and organ systems 10 – 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Here, we demonstrate the perfusion decellularization of a whole rat body as a proof of concept that this technology can decellularize any perfusable solid organ in situ. Currently, the ability to decellularize scaffolds from different organs in situ remains limited (Gerli et al, 2018;Kajbafzadeh et al, 2015). Using both harvested (traditional) and non-harvested (in situ) perfusion, decellularized organs showed the preservation of the vascular conduits, organ capsules, ECM components, and structural architecture, and presented low levels of DNA, while preserving the glycosaminoglycan, chemical and mechanical components of the ECM.…”
Section: Introductionmentioning
confidence: 99%
“…The work of Franklin Mall over a century ago 1,2 as well as modern day decellularization techniques 3 demonstrate that there are "reticular networks" made up of collagens, elastin, glycosaminoglycans, and other extracellular matrix (ECM) components surrounding, within, and between organs. These networks have biological and mechanical roles in defining the architecture and physiology of organs and, as a result, are now used as scaffolding for the creation of customized organ grafts for regenerative medicine.…”
Section: Introductionmentioning
confidence: 99%
“…5 More recently, decellularization of entire fetal sheep shows that the connective tissue network is continuous throughout the body and that the connective tissue of nerves creates structural continuity between the nervous system and other tissues. 3 Dissection of human bodies likewise demonstrates continuity across large, multiorgan regions of the body, including the entirety of the dermis and the fascia of diverse organs and organ systems. 6,7,8,9 Clinical disciplines including osteopathy have suggested that these connective tissue networks contain fluid and represent a body-wide communications network, akin to interstitial spaces, although this lacks detailed microscopic confirmation.…”
Section: Introductionmentioning
confidence: 99%